Estado e proteção social no Cone Sul da América Latina: um panorama do século XXI - Nayara Cristina Bueno; Lislei Teresinha Preuss (Ciências Sociais Unisinos)
The discussion on social protection in Latin America must consider the economic, social and political characteristics of the region, which have been historically constructed and reconstructed in the movement of peripheral capitalist society. In order to reflect on the relationship between the State and social protection in the beginning of the 21st century, this essay presents an overview of the conflict between capital and labor to directing the State, through social protection / public social unprotection. It presents characteristics of the Latin American society and the movement of the State in the 21st century, between the expansion and retraction in social investments. The coups d’état is analyzed as attempts to contain social advances and maintain the status quo, guaranteeing the privileges of groups linked to the ruling class and international financial capital. Finally, it demonstrates the need to transform the shape of public social protection in the Southern Cone of America to overcome the current challenges.